Laju Fotosintesis dan Kandungan Klorofil Kedelai pada Media Tanam Masam dengan Pemberian Garam Aluminium - PROKLAMASININGSIH, ELLY; PRIJAMBADA, IRFAN DWIDYA; RACHMAWATI, DIAH; SANCAYANINGSIH, RETNO PENI (Agrotrop : Journal on Agriculture Science, 2013)
The solubility of aluminum (Al) which is high in acid soils is unavoidable. Solutions or strategies that can minimize the adverse effect of Al on soybean need to be obtained, by studying the response of plants to Al. Al intoxication is a limiting factor for plant productivity. The purpose of this research was to study the effects of salt form of aluminum complexes with organic acids and salts of aluminum complexes with inorganic acids on the rate of photosynthesis and chlorophyll content of soybean (Glycine max) in the acidic growth medium. Research has been carried out experimentally in the greenhouse of Agriculture Faculty Gadjah Mada University. The design used was Completely randomized design (CRD) with factorial pattern, and two-factors. The first factor was the kind of aluminum salt consisting of three kinds: without Al, Al-nitrate salt and Al-lactate salt. The second factor is the level of medium acidity (pH) of growth medium with three level of pH value: pH 4, pH 5 and pH 6. Each treatment was repeated 3 replications. Variables that were observed included leaf area, the rate of photosynthesis and chlorophyll content. The results showed that the salt form of Al may affect rate of photosynthesis and chlorophyll content. complex Al salt form with organic acids (Al-lactate) can cause photosynthesis rate compares favorably with the Al-nitrate.
Keywords: photosynthesis rate, chlorophyll content, soybeans, acidic growth medium, aluminum salt